A gradient-directed adaptive algorithm for synchrotron radiation angiography - Carrato, S.; Sicuranza, G.L. (Mediterranean Electrotechnical Conference - Melecon, 1991, 1991)
An adaptive algorithm for the processing of digital subtraction angiographies obtained via synchrotron radiation is presented. In order to enhance the coronary arteries hidden by the heart chambers and the aorta, an adaptive high-pass filter is used. For each pixel of the image, the size of the filter is chosen according to the value of a gradient operator, which is computed over a large window centered on the same pixel. The algorithm has been successfully tested on some synthetic images and an image taken from a human subject.< >